Oil Price Volatility and Renewable Energy Consumption in Nigeria - Ayodele, Mercy Toluwase; Alege, Philip O. (International Journal of Energy Economics and Policy, 2021)
Oil price volatility is argued to be one of the incentives behind the rising prominence of renewable energy as a strategy to minimize oil dependence. Therefore, this study seeks to examine the impact of oil price volatility on renewable energy consumption in Nigeria from 1986-2017. A Vector Error Correction Model (VECM) was employed to achieve this objective. The variables were confirmed to exhibit a long run association. A unidirectional causality was also observed running from renewable energy consumption to oil price volatility. The impulse response function test shows that renewable energy consumption is positively influenced by oil price volatility in Nigeria. The variance decomposition result shows that real GDP causes the largest variation in renewable energy consumption amongst all the variables employed. The study recommends that public policies should be put in place to create awareness about the importance of the renewable energy sector and its potentials to lower health cost, mitigate climate change and helps Nigeria to attain energy security in the long run. Keywords: Oil Price Volatility, Renewable Energy Consumption, Vector Error Correction Model, Nigeria JEL Classifications: K32, P18, Q28 DOI: https://doi.org/10.32479/ijeep.9376